The Employment Effects of the EU Eastern Enlargement in Germany - Tobias Brändle; René Kalweit (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
In this paper, we empirically analyse the employment effects of the EU Eastern Enlargement of the EU in 2004. The integration of Central and Eastern European countries involves a massive reduction in both import and export tariffs; however, most of it happens before the actual ascen-sion event. Consequently, a large number German firms both increase their exports to and im-ports from the new EU member states in the time period between 1996 and 2010. The tariff reductions differ between industries and certain groups of firms are differently affected by the liberalisation. Exporters may benefit in terms of employment, while other firms might suffer from the increase in import competition.
Keywords: F14; J23; F66; 330